Trajectories of disability and influence of contextual factors among adults aging with HIV: Insights from a community-based longitudinal study in Toronto, Canada - Tai-Te Su; Ahmed M. Bayoumi; Lisa Avery; Soo Chan Carusone; Ada Tang; Patricia Solomon; Aileen M. Davis; Kelly K. O’Brien (PLoS ONE, 2025)
Background Individuals aging with HIV may experience disability that is multidimensional and evolving over time. Our aims were to characterize the longitudinal trajectories of disability and to investigate how intrinsic and extrinsic contextual factors influence dimensions of disability over an eight-month period among adults aging with HIV. Methods We analyzed longitudinal observational data from a community-based study in Toronto, Canada, where adults aging with HIV completed self-reported questionnaires over eight months (five time points). We measured disability using the Short-Form HIV Disability Questionnaire (SF-HDQ), which included six dimensions: physical, cognitive, mental-emotional health challenges, uncertainty, difficulties with day-to-day activities, and challenges to social inclusion. Higher SF-HDQ scores (range: 0–100) indicate greater severity of disability. We assessed intrinsic (age, gender, education, living status, number of comorbidities, mastery) and extrinsic (stigma, social support) contextual factors using baseline self-reported questionnaires. Latent class growth analysis was performed to identify distinct disability trajectories within each of the six dimensions. Multinomial logistic regression models were used to assess the influence of contextual factors on the disability trajectories. Results Of 108 participants, 89% identified as men with a mean age of 50.6 years (standard deviation ±10.9). We identified three disability trajectories: low, medium, and high disability severity in the physical, mental-emotional, and day-to-day activities dimensions. Four trajectories: low, medium-low, medium-high, and high disability severity were in the cognitive, uncertainty, and social inclusion dimensions. Factors such as higher self-mastery and social support were associated with lower disability trajectories, whereas greater number of comorbidities and stigma were associated with more severe disability trajectories over time. Conclusion Disability experiences among adults aging with HIV included three or four distinct trajectories with considerable heterogeneity over time. Information on contextual factors may be helpful for informing interventions and supports that mitigate disability among adults aging with HIV.